BREXIT REFERENDUM OF EUROPEAN UNION - Laode Muhamad Fathun (Dinamika Global, 2020)
This paper describes the phenomenon Brexit or Britain Exit on the future of EU regionalism and its impact on Indonesia. This paper will explain in detail the reason for the emergence of a number of policies Brexit. Brexit event caused much speculation related to Brexit in the European Union. The policy is considered full controversial, some experts say that Brexit in the European Union (EU) showed the independence of Britain as an independent state. Other hand, that Britain is the "ancestor" of the Europeans was struck with the release of the policy, meaning European history  can  not  be  separated  from  the  history  of  Britain.  In  fact  the above reasons that Britain came out associated with independence as an independent state related to EU policies that are too large, as a result of the policy model is very holistic policy while Britain desire is wholistic policy,  especially  in  the  economic,  political,  social  and  cultural.  In addition,  the  geopolitical  location  of  the  EU  headquarters  in  Brussels who also became the dominant actor in a union policy that demands as EU  countries  have  been  involved  in  the  formulation  of  development policy, including controversial is related to the ration immigrants. Other reason is the prestige associated with the currency. Although long since Britain does not fully adopt the EU rules but there is the possibility in the EU currency union can only occur with the assumption that the creation of functional perfect integration.